Unveiling Respiratory Pathogens: Insights from the Multiplex PCR FilmArray™ Respiratory Panel - Young Jun Hong; Bo Kyeung Jung; Jae Kyung Kim (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
This study aimed to evaluate the efficacy of the FilmArray™ Respiratory Panel (RP), a multiplex PCR test capable of simultaneously screening for 20 different pathogens. Upper respiratory tract infections (URTIs) are commonly caused by a variety of pathogens, leading to diagnostic challenges due to overlapping symptoms. Rapid and precise diagnostic tests are essential for effective treatment planning. Traditional culture-based diagnostic methods, while reliable, are hindered by their dependence on skilled personnel and lengthy processing times. In contrast, multiplex polymerase chain reaction (PCR) techniques provide enhanced accuracy and speed in identifying respiratory pathogens. The study was conducted at Dankook University Hospital in South Korea, this retrospective analysis spanned from January 2018 to December 2022 and included samples from patients presenting with upper respiratory tract infections. The results revealed that adenovirus was the most prevalent pathogen, identified in 18.9% of cases, followed by influenza virus A at 16.5%. Notably, a co-infection rate of 22.5% was observed. The FilmArray™ RP method successfully identified 20 pathogens within 2 hours, enabling prompt treatment decisions and reducing unnecessary antibiotic prescriptions. The integration of advanced diagnostic technologies, such as the FilmArray™ RP, in routine clinical practice is paramount for accurate pathogen identification and effective patient management. Overall, this study contributes to the growing body of evidence on the epidemiology of upper respiratory tract infections, offering foundational data that can support evidence-based decision-making in public health. This study highlights the significant advantages of multiplex PCR in the identification of respiratory pathogens, providing valuable insights for both epidemiological surveillance and clinical diagnosis.